Teknik Cetak Resin Dalam Pembuatan Sarana Upakara Pengabenan Dan Petulangan Di Rugos Art & Casting: Resin Printing in the Production of Ritual Offerings for Cremation at Rugos Art & Casting - i dewa, gede adikresna; Dana, I Nnyoman; Agung Jaya CK, I Gusti Ngurah (Hastagina : Jurnal Kriya Seni, 2024)
The human body is enlivened by the soul, allowing the body to move and function in this universe. When the soul leaves the human body, that is when a person dies. The relatives and family feel the loss, and thus, a form of respect is carried out through a ceremony, according to the customs, beliefs, or religion of the deceased. In general, the Balinese people, who are predominantly Hindu, conduct a burial ceremony. Ngaben is a cremation ceremony aimed at expediting the return of the elements present in the human body (earth, fire, water, air, and space) to their original state. The Ngaben ceremony requires certain facilities such as offerings for the ceremony and a structure called "bade," which serves as a container for the corpse, carried to the cemetery and then burned. The construction of the bade is carried out cooperatively by the Hindu Balinese community, so the Ngaben ceremony can be conducted promptly. However, with modern times, constructing the bade through communal efforts has become challenging due to people's busy schedules and individual workloads. Thus, there is a need for new technology to expedite the construction of the bade, such as using ornaments as decorative elements on the bade. The presence of human and animal figurines on the bade and the time-consuming process required for their creation can take several days to complete. The resin casting technology, developed by Rugos Art & Casting, produces various forms of artistic works. Observing this, students are interested in undertaking fieldwork practice in resin casting, aiming to produce resin casts to speed up the creation of animal head forms. This would expedite the ornamentation process for the bade, making the Ngaben ceremony timelier and more efficient, thus ensuring it is conducted according to plan.